2012
DOI: 10.1155/2012/253693
|View full text |Cite
|
Sign up to set email alerts
|

Tophaceous Gout of the Patella: A Report of Two Cases

Abstract: Introduction. Tophaceous gout of the patella is rare and may masquerade as a tumour or tumour-like condition. Cases. We report two patients with gout involving the patella, one complicated by a pathological fracture and the other occurring in a bipartite patella in a young adult. Discussion. Typical imaging appearances and measurement of serum urate will usually confirm the diagnosis but, occasionally, the serum urate level may be normal in active gout and in such cases, a biopsy will be required. Conclusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The knee is the third most commonly affected site in gout after the foot and ankle [10]. However, isolated patellar involvement, especially leading to the patellar fracture, was rarely reported [1][2][3][4][5][6][7][8][9]. Tophaceous gout of the patella was first reported by Peloquin and Graham who in 1955 described a patient with erosion of the patella at surgery [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knee is the third most commonly affected site in gout after the foot and ankle [10]. However, isolated patellar involvement, especially leading to the patellar fracture, was rarely reported [1][2][3][4][5][6][7][8][9]. Tophaceous gout of the patella was first reported by Peloquin and Graham who in 1955 described a patient with erosion of the patella at surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological fracture of the patella caused by gout is pretty rare. Only sporadic published articles have reported pathological patellar fracture due to gout during the last several decades [1][2][3][4][5][6][7][8][9]. In this paper we report a case of gout tophi in the left patella and surrounding soft tissue, the severe transverse fracture resulting from relatively minor trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Bone erosions typically occur at the sites of tophi formation [4]. Gout involvement of the extensor tendons of the knee is not uncommon, but involvement of the patella is rare [5], [6].…”
Section: Discussionmentioning
confidence: 99%
“…Ko et al 7 evaluated the locations and associated erosions of tophaceous gout in knees of 30 patients and detected only one intraosseous tophus in the patella. Hopper et al 8 reported two patients with gouty involvement of patella with pathological fracture and bipartite patella. We were able to find only one case report in the English literature with bilateral lesions of patellae similar to our case.…”
Section: Discussionmentioning
confidence: 99%